2020
DOI: 10.3390/ijerph17176221
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Socio-Demographic Correlates of Food Insecurity in Poland

Abstract: While food insecurity (FI) has been extensively studied in many countries, there have been few empirical contributions in Poland to date. The main objective of our research was to identify the socio-demographic factors affecting the risk of FI in Poland within 2014–2019. Moreover, we aimed to examine the effects of the family-oriented social program “Family 500+” by comparing the situation in various types of households with children a few years before and after the program was launched. The analysis was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
4
17
0
2
Order By: Relevance
“…We found that parents’ higher age (over 50), higher parents’ school grade, and both parents being employed were protective against FI. Similar protective factors had already been identified in several studies before the pandemic [ 37 , 38 ]. Recently, an Australian online survey, performed between May and June 2020 on 1170 adults living in Tasmania, found that increasing age, a university education and higher income were protective against FI [ 39 ].…”
Section: Discussionsupporting
confidence: 81%
“…We found that parents’ higher age (over 50), higher parents’ school grade, and both parents being employed were protective against FI. Similar protective factors had already been identified in several studies before the pandemic [ 37 , 38 ]. Recently, an Australian online survey, performed between May and June 2020 on 1170 adults living in Tasmania, found that increasing age, a university education and higher income were protective against FI [ 39 ].…”
Section: Discussionsupporting
confidence: 81%
“…As one can see from Table 1, farmers, rural communities and the most valued issue for them are the main points of reference in assessing risks of agricultural systems in the face of covid-19 pandemics. Ahmed et al, 2020;Barcaccia et al, 2020;Barichello, 2020;Martin, 2020;Mitaritonna & Ragot, 2020;Neef, 2020;Nicola et al, 2020;Phillipson et al, 2020 Social implications Overall food insecurity and hunger Deaton & Deaton, 2020;Dudek & Myszkowska-Ryciak, 2020;Kent et al, 2020;Laborde et al, 2020aLaborde et al, , 2020bLal, 2020a;Lal et al, 2020;Neff, 2020;Niles et al, 2020;Owens et al, 2020;Torero, 2020;Wolfson & Leung, 2020;Zavaleta-Cortijo et al, 2020 Source: Created by authors.…”
Section: Collecting Preparing and Analyzing Informationmentioning
confidence: 99%
“…The covid-19 has the most severe impacts on these groups of people. The most studies (Dudek & Myszkowska-Ryciak, 2020;Leddy et al, 2020;Marcus et al, 2020;Neff, 2020;Owens et al, 2020) dealing with social issues of covid-19 in agriculture have highlighted the negative impact of food risks to pour people and homeless people as well as negative health consequences to most vulnerable people groups (Abrams & Szefler, 2020;Poudel & Subedi, 2020;Singh et al, 2020). Some authors (Ahmed et al, 2020;Laborde et al, 2020aLaborde et al, , 2020b noticed that poverty and food insecurity is expected to grow dramatically due to Covid-19 pandemic.…”
Section: Vulnerability Of Agricultural Systems To Covid-19 Pandemicmentioning
confidence: 99%
“…The health status of individuals was negatively affected as animal foods were consumed less in the households, one-fifth of households did not consume milk, dairy products, and eggs daily, and nutrition was mostly based on bread consumption. Food insecurity can lead to a worse health status as it affects the nutritional value and quantity of selected foods (26) . For example, one study determined that approximately one-third of families purchased high-calorie snacks and desserts more often during the pandemic period (19) .…”
Section: Discussionmentioning
confidence: 99%